Atypical inflammatory demyelinating syndromes of the CNS - Hardy, T; Reddel, S; Barnett, M; Palace, J; Lucchinetti, C; Weinshenker, B (Elsevier, 2016)
Atypical inflammatory demyelinating syndromes are rare disorders that differ from multiple sclerosis owing to unusual clinical or MRI findings or poor response to treatments used for multiple sclerosis. These syndromes include neuromyelitis optica spectrum disorder, acute disseminated encephalomyelitis, tumefactive demyelination, Baló's concentric sclerosis, Schilder's disease, and Marburg's multiple sclerosis. The overlapping features of these syndromes with multiple sclerosis and with each other complicate diagnosis and their categorisation as distinct or related conditions. Recognition of these syndromes is crucial because they differ from multiple sclerosis and other demyelinating and non-demyelinating conditions in their prognosis and treatment. Advances in MRI, pathology, and immunobiology are needed to increase understanding of these syndromes, including the extent to which some of them represent distinct entities, and to assist with improvements in their diagnosis and management.